Enhancing the clinical supervision experience of staff members working within primary and community care: a best practice implementation project. (11th September 2022) - Smith, Cathryn; Bennett, Clare; Morgan, Kate; Carrier, Judith; Klugarová, Jitka; Klugar, Miloslav
ABSTRACT: Objectives: The project aimed to assess compliance with evidence-based criteria regarding the use of clinical supervision amongst district nurses and to improve knowledge and engagement in clinical supervision activities within the workplace. Introduction: It is important to provide clinical support to all healthcare workers that provide opportunities to develop and be listened to in a supervised environment. Clinical supervision is seen as a key element to provide this support. It provides a professional working relationship between two or more members of staff where the reflection of practice and personal emotion can be discussed, which is outlined in many policies and guidelines. Methods: A baseline audit was carried out using the JBI Practical Application of Clinical Evidence System program involving 16 participants in one district nursing team in South Wales. The first step involved the development of the project and generating the evidence. Following this, a baseline audit was conducted, and educational training on clinical supervision was undertaken followed by clinical supervision sessions. A postimplementation re-audit was conducted following implementation. Results: A total of 16 participants enrolled on the project. Receiving basic training and participating in clinical supervision was much higher than the baseline audit with both increasing to 100% compliance. Furthermore, 94% of participants were aware of clinical supervision activities and 88% knew of existing records on clinical supervision. The project results show a large increase in compliance with all of the criteria. Conclusion: Overall the implementation project achieved an improvement in evidence-based practice regarding clinical supervision in primary care.